Sebaran Infeksi Leptospira Patogenik pada Tikus dan Cecurut di Daerah Pasca Banjir Kabupaten Pati dan Endemis Boyolali - Zumrotus Sholichah; Rahmawati Rahmawati (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2017)
Until March 2014 leptospirosis cases and its Case Fatality Rate increased in Pati and Boyolali. This study aims to describe distribution of infected rats and shrews in flood area in Pati and endemic area in Boyolali. Research carried out by the cross sectional design on March-April 2014. Coordinate of Leptospira infected rats and shrews were mapped using google earth with home range buffer. Data analyzed descriptively to describe distribution of infected rats and shrews. Pathogenic Leptospira sp. infected rats and shrews spread with random pattern. This results could be an explanation of higher transmission risk. of leptospirosis in the area of study